Semiotics of space in ecological agroarchitecture - Ostapenko, I.I.; Seitova, N.S.; Dyussenova, D.G.; Yessenbayev, A.M. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2025)
In the context of worsening environmental problems, modern architecture is turning to the search for new models of interaction with nature. Ecological agroarchitecture, combining sustainable design, agrotechnology and the philosophy of nature-oriented thinking, is becoming one of the relevant areas. The purpose of this study is to consider the architectural space of the agroecological type as a semiotic system capable of translating the values of sustainability, memory and cultural identity. The work focuses on objects where the principles of bioesthetics, environmental ethics and symbolic expression intersect, such as energy – intensive buildings, memorial complexes and biomorphic pavilions. The methodology is based on an interdisciplinary approach combining architectural semiotics, environmental design and cultural and philosophical analysis. The results show that architectural forms of agroarchitecture have symbolic potential: they visualize natural processes and convey the ideas of cyclicity, rebirth and belonging. The research contributes to the development of the concept of architectural space as a meaningful system and can be applied in the design of objects integrated into the ecological and cultural context.